ISCHEMIC STROKE IN THE VERTEBRAL-BASILAR BASIN AGE AND GENDER CHARACTERISTICS OF EARLY REHABILITATION (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
This article is devoted to the analysis of age and gender characteristics in the process of early rehabilitation after ischemic stroke in the vertebral-basilar basin. The study shows the influence of age and gender on the speed and quality of a patient's recovery and sheds light on the importance of these factors in the rehabilitation process. Since young patients, especially children and adolescents, can recover faster after a stroke, brain plasticity and high flexibility of the neurological system are important factors in the rehabilitation process. For older people, on the contrary, the rehabilitation process slows down due to other health problems and low plasticity. Depending on gender, men need more physical recovery, and women need cognitive and psychological recovery. The article analyzes the effectiveness of age- and gender-appropriate rehabilitation methods based on scientific literature, and emphasizes the need for individual approaches to optimize the rehabilitation process of patients. The article highlights the importance of developing age- and gender-sensitive rehabilitation programs and serves to increase patients' chances of recovery in healthcare systems.